COMBINED IL-2/IL-3 GENE THERAPY FOR G422 MOUSE GLIOBLASTOMA BY INTRATUMORAL INJECTION OF RECOMBINANT ADENOVIRUSES1 - Hong, Bo; Cao, Xuetao; Yu, Yizhi; Zhang, Weiping; Lei, Hong (Chinese Journal of Cancer Research, 2013)
Recombinant adenoviruses encoding murine IL-2 gene or IL-3 gene were directly injected into established subcutaneous tumor model of G422 glioblastoma cells. After treatment, the tumor size and survival of the gliohlastoma-bearing mice were observed. The splenic NK and CTL cytotoxicities were detected by standard 4- hour 51Cr release assay. We also examined the histopathological changes of tumor by hematoxylin and eosin staining. The results showed that intratumoral injection of adenoviruses encoding murine IL-2 gene or IL-3 gene significantly inhibited the growth of G422 glioblastoma and prolonged the survival period of glioblastoma-bearing mice. The CTL cytotoxicity of the gene therapy groups was significantly higher than that of the control groups, but NK activity remained unchanged, indicating that specific immunity contributes to the in vivo antitumor effect of the direct gene therapy. There were much more tumor necrosis and inflammatory cell infiltration in the tumor of the gene therapy groups. Combined IL-2/IL-3 gene therapy could induce higher level of CTL and enhance the therapeutic potential further. The results suggest that intratumoral injection of recombinant adenoviruses encoding certain kind of cytokines may be a useful approach in the treatment of a malignancy of the central nervous system.